Stability Analysis of Metro Kapsul Based on Multibody System Using Universal Mechanism - ADONIA IDNANI (NIM : 13114131), SIDHART
Metro Kapsul is one type of transportation produced by PT. Engineering Train Kapsul Engineering as one solution to traffic problems in Bandung. Before it can operate, a series of analyzes and technical evaluations are needed to ensure the feasibility and safety of the vehicle. One of them is the stability analysis. This final project will compare stability analysis using SIMPACK and Universal Mechanism software. From these results, a comfortable and safe operating condition will be determined based on ANSI / ASCE / T & DI 21.2-08. Research begins with literature studies, discussions, data collection, and formulation of loading cases. From the formulation of the loading case, a theoretical calculation of the loading cases was carried out. After that, the Metro Capsules multibody model was made. This model is validated by comparing theoretical and simulations value of normal force and natural frequency of the system. If the result is valid, the results can be determined. There are differences in the simulation results using SIMPACK and Universal Mechanism. The value of the simulation using Universal Mechanism results tends to be higher than the value of the simulation using SIMPACK. The longitudinal acceleration of Metro Kapsul operation is 0.90 𝑚𝑠2⁄, the longitudinal slowing operation is 0.97 𝑚𝑠2⁄, and the emergency longitudinal acceleration is 1.25 𝑚𝑠2⁄. For turning circumstances, the lateral operating acceleration is 0.98 𝑚𝑠2⁄. Thus, the speed of the Kapsul Metro at a turn is 13.8 km / h at a radius of 15 m and rises steadily until the winding speed is 31.89 km / h at a radius of 80 m.